Chemokines as key mediators in RIPI: pathophysiology and translational potential - Zhao, Ling; Dong, Lihua; Hou, Xue; Fu, Weijia; Wei, Jiaying; Liu, Wentong; Hou, Wei (Frontiers in Immunology, 2025)
Radiation-induced pulmonary injury (RIPI) is a common adverse effect following thoracic radiotherapy (RT), and immune-related responses play a pivotal role in the pathogenesis of RIPI. Chemokines are important components of the human immune system which could modulate inflammatory responses. Their levels fluctuate following radiation. These chemokines recruit relevant immune cells, such as macrophages and lymphocytes, and induce lung inflammatory responses. In addition to early-stage inflammation, chemokines are also associated with radiation-induced pulmonary fibrosis (RIPF) at a late stage and can augment the risk of post-radiation lung metastasis. Because of the correlation between chemokines and RIPI, chemokines may be useful for RIPI diagnosis and treatment. This review aims to summarize the alterations of the levels of different chemokines after radiation, the regulatory mechanisms, and the advancements of research on the diagnosis and treatment of RIPI by chemokines, in order to provide references for the subsequent RIPI research.